How Did Students Perceive Classroom Learning under Strict COVID-19 Pandemic Closures and Restrictions? - Sako, Takayoshi (Universitas Nusantara PGRI Kediri, 2021)
The COVID-19 pandemic of 2020 required strict infection prevention measures worldwide, including school closure. After school reopened, we implemented Japan’s strict COVID measures, under which close contact in pairs or groups, as well as vocalizing in unison, was proscribed, with students having to remain quiet and face the blackboard. This study’s aim is to answer the question of how students felt about learning under such extreme constraints. One of the most noticeable findings from the responses to the survey of the 2020 class was that they felt the lack of collaborative learning experiences; hence, in 2021, we implemented changes that would allow for more collaboration while still adhering to COVID prevention guidelines. Among the various collaborative learning activities in the classroom, students reported that they found value in debate activities that challenged their English language skills and critical thinking. Overall, however, students found comfort and value in a semblance of learning with their peers. It was concluded that even in a volatile and uncertain situation, such as a pandemic, it is crucial to improve environments for collaborative learning. In the future, quantitative study of the impact of collaborative learning on students’ English proficiency will be a useful follow-up study.